Carbapenem-Resistant Citrobacter spp. as an Emerging Concern in the Hospital-Setting: Results From a Genome-Based Regional Surveillance Study - Yao, Yancheng; Falgenhauer, Linda; Falgenhauer, Jane; Hauri, Anja M.; Heinmüller, Petra; Domann, Eugen; Chakraborty, Trinad; Imirzalioglu, Can (Frontiers in Cellular and Infection Microbiology, 2021)
The rise of Carbapenem-resistant Enterobacterales (CRE) represents an increasing threat to patient safety and healthcare systems worldwide. Citrobacter spp., long considered not to be a classical nosocomial pathogen, in contrast to Klebsiella pneumoniae and Escherichia coli, is fast gaining importance as a clinical multidrug-resistant pathogen. We analyzed the genomes of 512 isolates of 21 CRE species obtained from 61 hospitals within a three-year-period and found that Citrobacter spp. (C. freundii, C. portucalensis, C. europaeus, C. koseri and C. braakii) were increasingly detected (n=56) within the study period. The carbapenemase-groups detected in Citrobacter spp. were KPC, OXA-48/-like and MBL (VIM, NDM) accounting for 42%, 31% and 27% respectively, which is comparable to those of K. pneumoniae in the same study. They accounted for 10%, 17% and 14% of all carbapenemase-producing CRE detected in 2017, 2018 and 2019, respectively. The carbapenemase genes were almost exclusively located on plasmids. The high genomic diversity of C. freundii is represented by 22 ST-types. KPC-2 was the predominantly detected carbapenemase (n=19) and was located in 95% of cases on a highly-conserved multiple-drug-resistance-gene-carrying pMLST15 IncN plasmid. KPC-3 was rarely detected and was confined to a clonal outbreak of C. freundii ST18. OXA-48 carbapenemases were located on plasmids of the IncL/M (pOXA-48) type. About 50% of VIM-1 was located on different IncN plasmids (pMLST7, pMLST5). These results underline the increasing importance of the Citrobacter species as emerging carriers of carbapenemases and therefore as potential disseminators of Carbapenem- and multidrug-resistance in the hospital setting.